Migration of neuroblasts from neurogenic placodes. - Begbie, J (2008)
Peripheral neurons involved in cephalic sensory systems are born in the ectoderm at a distance from the neural tube. The neuroblasts migrate internally, coalesce to form ganglia and extend axons to the central nervous system. This process has long been evident but little is known about the way it occurs. We have shown that coordination of the migration and integration with the hindbrain occurs through interaction with neural crest cells.